Deironing of underground water with modified refractory chamotte - Pavel A. Klebeko; Valentin I. Romanovski (Водное хозяйство России: проблемы, технологии, управление)
Water from underground sources in Russia and the CIS countries mainly contains higher concentrations of iron and manganese. With a permissible rate of iron content in drinking water of 0.2–0.3 mg/L, its content in groundwater can reach 40 mg/L. To remove excess soluble iron, it is oxidized to insoluble forms. For these purposes, iron removal filters are used. This research describes the preparation of modified catalytic material to intensify the process of deferrization of underground water.